Developing and testing an instrument to assess aquaticity in humans. Issue 3 (July 2016) - Varveri, Danae; Flouris, Andreas D.; Smirnios, Nikitas; Pollatou, Elizana; Karatzaferi, Christina; Sakkas, Giorgos K.
Summary: We developed and validated an aquaticity assessment test (AAT) for the evaluation of human physical adequacy in the water. Forty-six volunteers (25M/21F; 20 ± 8 years) participated and performed 10 easy-to-administer and practical aquatic tasks. Group A was formed by 36 elite athletes (M/F 20/16, 24.7 ± 10yrs) from two sports categories depending on their affinity to the water environment: terrestrial (wrestling, cycling, dancing) and aquatic (swimming, synchronized swimming, free diving) sports. Group B was formed by 10 non-athlete participants (5M/5F, 14.4 ± 1.4yrs) and was assessed by two independent evaluators. Participants in Group A performed the aquatic tasks once to develop the final AAT items and cutoffs. Participants in Group B performed the aquatic tasks twice on different days to assess repeatability. Factor analysis recommended all 10 aquatic tasks to be included in the final AAT, resulting in scores ranging from 9.5 to 49.5. The AAT scores were statistically different between the terrestrial and the aquatic sports' participants (p < 0.001). The duration of the test was 25 min from the time of water entry. Receiver operating characteristics curve analyses demonstrated that the cutoffs for low and high aquaticity levels in this sample were ≤23.7 and ≥43.3, respectively. Reliability analyses demonstrated that the aquaticity scores obtained on different days and by different examiners highly correlated (p < 0.001) and were not significantly different (p > 0.05). The AAT appears to be a valid and reliable tool for the evaluation of human physical adequacy in the water. It is an easy and user-friendly test which can be performed in any swimming pool without a need for highly trained staff and specialized equipment, however more research needs to be done in order to be applied in other population group.